The Challenge of Sustainability: Turning Science into Art - Mishra, Satish Chandra (The Indonesian Forestry Certification Cooperation, 2022)
This paper addresses the critical question of how to turn climate concern into climate action as we move forward towards the 1.5 degree Celsius global warming target adopted by COP 26 in 2021 and reaffirmed by COP 27 in 2022. It argues that it has taken scientists more than a Century to accept, first: that climate change is real and second: that it is anthropogenic. Scientists still continue to debate the precise effects of greenhouse gases on weather, fires, floods and food security. Climate optimists continue to rely on the search for new miracle technologies, such as fusion energy or carbon capture. This is all very good. But this is the easy part. What is more critical is to motivate people towards collective action in pursuit of a zero-emission target. This requires harnessing the art of fostering humanist, economically just, collective action rooted in local commitment and transparency. The real challenge of sustainability today is to turn science into art. We do not have over a century and half, as the scientists did to practice this art. Repeatedly, pointing to climate change apocalypse will not be enough.